Full- and Part-Time Wage Differentials and Female Labor Supply: Discontinuous Budget Constraint and Endogenous Wages - Myeong-Su Yun (Rutgers University, Department of Economics, 2000)
We introduce a structural model which jointly estimates the full-time wage premium and female labor supply, using the piecewise-linear budget constraint method. Our model incorporates a discontinuous budget line at cut-off hours (35 hours a week), caused by the coexistence of both full- and part-time wage rates, and makes wages fully endogenous to the labor supply choice. We estimate a structural model using the female sample from March 1995 current population survey. The estimate of the full-time premium from our structural model is slightly larger than that of OLS, while Heckman's two-step method predicts a small full-time wage premium. Our estimates for labor supply elasticities lie within the ranges reported in previous research.
Keywords: C34; J22; J31; 330; discontinuous budget line; endogenous wages; female labor supply; full-time wage premium; piecewise-linear budget constraint method